1986
DOI: 10.1002/maco.19860370906
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of copper by food acids containing colourants and sweetening agents – Part II: Corrosion by tartaric acid

Abstract: The corrosion of copper in tartaric acid solutions containing various food colourants and/or sweetening agents has been studied with respect to the concentration of the acid and the colourant, and temperature. At constant acid concentration the corrosion increases with the concentration of the colourant whereas at constant colourant concentration it increases with acid concentration. In acid solutions the corrosivity of the colourant increases in the order: tartrazine < ponceau 4R < carmoisine < amaranth < fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Examples of compounds likely to inhibit corrosion in food media are antioxidants such as ascorbic acid, and even folic acid, which is not an antioxidant [ 8 , 9 , 10 ], while plausible corrosion enhancers are some of the organic acids present in foods. Some reports [ 11 , 12 , 13 ] appear to suggest that sulphide compounds in fruits and foods can enhance corrosion. Furthermore, processing methods and the history of fruits can exert influences on the composition of the extracted juice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of compounds likely to inhibit corrosion in food media are antioxidants such as ascorbic acid, and even folic acid, which is not an antioxidant [ 8 , 9 , 10 ], while plausible corrosion enhancers are some of the organic acids present in foods. Some reports [ 11 , 12 , 13 ] appear to suggest that sulphide compounds in fruits and foods can enhance corrosion. Furthermore, processing methods and the history of fruits can exert influences on the composition of the extracted juice.…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid, a common component of fruits and fruit juices, has been reported to inhibit the corrosion of aluminium in 2 M NaCl (at pH 2) at concentrations ≤10 −5 M [ 16 ]. Talati and Patel [ 12 ] studied the effect of colourants and sweetening agents on copper corrosion in tartaric acid commonly present in various fruits and reported that all the food colourants and sweetening agents studied accelerate the corrosion of copper by tartaric acid. Adewuyi and Oladunjoye [ 40 ] studied the effects of sweeteners (glycerol, saccharin, glucose, and sucrose) and colourants (Carmoisine, Sunset Yellow, Poncreau 4R, and Tartazine) on tin-coated steel plates in malic acid and reported that while the sweetening agents inhibited corrosion, the colourants enhanced the corrosion of the tin-plated steels, and attributed the inhibitive effects of the sweeteners to the presence of hydroxyl groups that can form complexes with metal ions, which when insoluble can lead to corrosion inhibition [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%